Influence of drawbead geometry on sheet metal forming - Samuel, M (Journal of materials processing technology, 2002)
This paper describes a numerical model devised to determine the pull force, shear force and bending moment required to form sheet metal subject to plane strain along the width. This model is formulated to fit with the finite element package MARC. To simplify the analysis, it is assumed that the planes remain unchanged and always normal to the mid-surface, and the plane stress develops across the thickness. Bending, unbending and reverse bending of the strip during deformation is analyzed and the constitutive law for this cyclic process is discussed. The output of the model provides the geometry of the deformed shape, the forces and moments applied along the strip, and stress–strain distributions. The forces are expressed in terms of the drawbead geometry and coefficient of friction. The model is used for the investigations of blankholding conditions and friction on the deformation of the material which will be passed through the drawbead gap. The numerical results were found in good agreement with the experimental results.